Penggunaan Media Pembelajaran Visual untuk Meningkatkan Hasil Belajar Siswa di Madrasah Ibtidaiyah Negeri (MIN) 4 Desa Tanjung Genting Kabupaten Kerinci - Amrul Amrul (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
This study was conducted to determine whether visual learning media can improve student learning outcomes in Madrasah Ibtidaiyah Negeri (MIN) 4 Tanjung Genting Village, Kerinci Regency. The type of research used is Classroom Action Research (CAR). The research subjects were students of class V MIN 4 Kerinci. The data collection techniques used in this study include tests, observations, and interviews. While the data analysis technique is carried out in several stages, namely data reduction, data presentation, and verification or drawing conclusions. The results showed that there was an increase in student learning outcomes by using visual learning media. This can be seen from the Minimum Criteria Completeness (KKM) of students in each cycle. In cycle 1, the average score was 56.25. In the second cycle it increased to 66.25. Then in the third cycle obtained an average value of 78.12. Thus, it can be concluded that the use of visual learning media can improve student learning outcomes in Madrasah Aliyah Negeri (MIN) 4 DesaTanjung, Kerinci Regency.